2019
DOI: 10.3390/su11174773
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Purchase Intention toward Organic Food in an Asian Emerging Market: A Study of Urban Vietnamese Consumers

Abstract: This study aims to investigate some factors influencing purchase intention toward organic food among urban consumers in Vietnam, an Asian emerging economy. The extended Theory of Planned Behavior was used as theoretical framework for this study. In order to test the proposed model and hypotheses, a survey was conducted on a sample including 572 consumers in Hanoi, the capital city of Vietnam. The findings of structural equation modeling indicated that modern self, traditional self, health consciousness, organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 48 publications
6
54
0
Order By: Relevance
“…Other findings from the region, such as Nguyen et al [86], reveal that organic foods label significantly contributed to buyers' favorable attitude to buying organic foods among urban Vietnamese consumers, while Fogarassy et al [71] found that highly educated young people who are very conscious and live on good incomes may be the target group for circular innovation in Hungary. The study found that young consumers, the internet savvy, and software users living in cities buy organic foods and follow healthy lifestyle trends.…”
Section: Discussionmentioning
confidence: 98%
“…Other findings from the region, such as Nguyen et al [86], reveal that organic foods label significantly contributed to buyers' favorable attitude to buying organic foods among urban Vietnamese consumers, while Fogarassy et al [71] found that highly educated young people who are very conscious and live on good incomes may be the target group for circular innovation in Hungary. The study found that young consumers, the internet savvy, and software users living in cities buy organic foods and follow healthy lifestyle trends.…”
Section: Discussionmentioning
confidence: 98%
“…The TRA has proved to be an effective model that can explain and predict consumer attitude, intention, and behavior relating to food products including functional foods [30][31][32][33]. Given that subject norm was found to be a weak determinant of intention, several authors have suggested to examine the linkage between subjective norm and attitude [19,34,35]. Our research model, therefore, sought to extend the TRA by positing that subjective norm has a positive influence on attitude.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Understanding the barriers to functional foods purchase and acceptance (e.g., price) is essential to increasing consumer demand for these products [30]. Given that subject norm was found to be a weak determinant of intention, several authors have suggested to examine the linkage between subjective norm and attitude [19,34,35]. Our research model, therefore, sought to extend the TRA by positing that subjective norm has a positive influence on attitude.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations